Theoretical and methodological foundations for the training of physicians, internists, general practitioners (family doctors) - S. Yu. Astanina; R. N. Shepel; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
The current stage of Russian healthcare development is characterized by the progressive integration of various labor functions of primary care physicians with increasing intensity of professional activity. The solution to this problem should be under the banner of increasing the effectiveness of medical education and, above all, the training of physicians, internists, general practitioners (family doctors). The problem of determining the most effective methodological approaches to the management of training doctors is relevant.The aim of the study is to determine the theoretical and methodological foundations for training primary care doctors in a single educational space. The functioning of a unified educational space system is of crucial importance in the training of medical practitioners, internists and general practitioners (family doctors), which allows preserving the best traditions of the therapeutic school in the country and developing it in the future.